Explaining differences in English hospital death rates using routinely collected data. Issue 7197 (5th June 1999) - Jarman, Brian; Gault, Simon; Alves, Bernadette; Hider, Amy; Dolan, Susan; Cook, Adrian; Hurwitz, Brian; Iezzoni, Lisa I
Abstract : Objectives: To ascertain hospital inpatient mortality in England and to determine which factors best explain variation in standardised hospital death ratios. Design: Weighted linear regression analysis of routinely collected data over four years, with hospital standardised mortality ratios as the dependent variable. Setting: England. Subjects: Eight million discharges from NHS hospitals when the primary diagnosis was one of the diagnoses accounting for 80% of inpatient deaths. Main outcome measures: Hospital standardised mortality ratios and predictors of variations in these ratios. Results: The four year crude death rates varied across hospitals from 3.4% to 13.6% (average for England 8.5%), and standardised hospital mortality ratios ranged from 53 to 137 (average for England 100). The percentage of cases that were emergency admissions (60% of total hospital admissions) was the best predictor of this variation in mortality, with the ratio of hospital doctors to beds and general practitioners to head of population the next best predictors. When analyses were restricted to emergency admissions (which covered 93% of all patient deaths analysed) number of doctors per bed was the best predictor. Conclusion: Analysis of hospital episode statistics reveals wide variation in standardised hospital mortality ratios in England. The percentage of total admissions classified as emergencies is the most powerful predictor of variation in mortality. The ratios of doctors to head of population served, both in hospital and in general practice, seem to be critical determinants of standardised hospital death rates; the higher these ratios, the lower the death rates in both cases.